Performance Of Sintered Geopolymerised Palm Oil Fuel Ash And Water Treatment Sludge Lightweight Aggregate - Kwek, Shi Ying (2022)
Concrete has been acknowledged as the most preferred construction product mainly used in construction industry and aggregate is one of the essential constituents in concrete mixture. Huge consumption on natural aggregate for the development of construction industry have caused an issue on natural resource depletion and adverse impact on the environment. The utilization of industrial waste as building material will solve disposal problem and reduce the negative impact on the environment. Among the wastes, the cementitious property of palm oil fuel ash (POFA) as industrial waste contributes to the geopolymer based binder which needs to be fully exploited to be used as alternative building material. Incorporation of POFA with water treatment sludge to perform manufacture aggregate is scarcely explored. This study focuses on utilizing locally available waste materials namely POFA and silt as the raw materials, with 8 range of L/S ratio, activated by 6 range of alkaline ratio as coarse aggregate production for concrete application.